The Factors That Influence The Firm Performance In The Furniture Industry Jepara - . Mahmud; Guruh Taufan H; Ida Farida (UBL, 2013)
Furniture industryinJeparais one ofIndonesias main commoditiesto be proud ofandbe maintainedevenif itneeds to be improved. The industryoccupiesa strategicpositionof being ableto contributeto regional revenueby 26% byvalue ofexports ofU.S. 130million ormorethanRp1trillionin 2010andin 2011reachedU.S. 111.65million. However,exportsfromJeparafurnitureislikely to declinedue toa variety of things. This study aimstoanalyze firm performance through, market orientation, learning orientation, and innovationin furnitureindustryinJepara. The samplesin this study were110smallandmedium-sizedenterprises. Sixthhypothesis with SEManalysis resultsof the researchare: (1) learningorientationhave a significant effecton firm performance, (2) learningorientationsignificant effect oninnovation, (3) marketorientation havea significant effect oninnovation, (4) marketorientationsignificantly influence on firms performance, (5) innovationno significant effect on firm performance. Indicatorvariablesthatneed to be consideredinlearningorientationisopen-mindednessandsharingof knowledge, whiletheindicatorvariable of themarket-orientation is competitororientationasa significant effect oninnovationandfirm performance.